Evaluation of the Level of User Satisfaction of the I-Con Application (Aam Interactive Collection) Using the Pieces Method at PT Anugrah Argon Medica, Medan Branch - Retno Kiswati, Endratri; Br. Purba, Rahima; Maisyarah, Renny (International Journal of Business, Law, and Education, 2025)
The effectiveness of an accounting information system in a company depends significantly on human resource factors, particularly the user's ability to apply and understand the system. This study evaluates the I-CON application at PT Anugrah Argon Medica, Medan Branch, using the PIECES framework, which includes Performance, Information, Economic aspects, Control and Security, Efficiency, and Service quality. A quantitative approach was employed, gathering data through questionnaires distributed to 42 employees, with a census sampling technique applied. Data analysis was conducted using descriptive statistical methods, classical assumption tests, and hypothesis testing with SPSS. The findings revealed that not all factors significantly influenced user satisfaction. Performance (X1) showed no significant effect, highlighting the need for hardware and software upgrades to enhance system stability and speed. Conversely, Information (X2), Economic aspects (X3), Control (X4), Efficiency (X5), and Services (X6) positively impacted user satisfaction, emphasizing the importance of data accuracy, cost-effectiveness, security, operational efficiency, and responsive support services in improving user experience. These results suggest that companies must focus on these critical dimensions to enhance the effectiveness and user satisfaction of the I-CON application